TI_GERICHTE 11.2006.59 vom 9. August 2006 , Provvedimenti cautelari in vista di promuovere un'azione possessoria - TI Tribunale d'appello (2006)
Provvedimenti cautelari in vista di promuovere un'azione possessoria